2015
DOI: 10.1002/ijc.29627
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives toward the identification of key players in gastric cancer microRNA dysregulation

Abstract: Acquired genetic and epigenetic alterations in normal cells give rise to transformed cells, which lead to tumor development. Elucidation of the precise mechanisms underlying primary and metastatic tumor formation is required. MicroRNAs (miRNAs) are small noncoding RNAs that play a major role in post-transcriptional gene regulation during various biological processes. Accumulating evidence suggests that dysregulation of miRNAs is intimately involved in the carcinogenesis, progression and metastasis of many canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 152 publications
(153 reference statements)
1
26
0
Order By: Relevance
“…Overall, our results showed that miRNAs miR-103, miR-181c, miR-370 and miR-375 are down-regulated in chronic gastritis regardless of H. pylori infection, because both infected and non-infected sample groups had reduced expression of these miRNAs. Other studies have shown down-regulation of miRNAs in inflammatory gastric lesions infected or non-infected by H. pylori (Matsushima et al, 2011;Shiotani et al, 2012); however, in gastric cancer some studies have reported increased expression of miRNAs such as miR-103, miR-181c, miR-370, miR-21 and miR-146a (Wu et al, 2011;An et al, 2013;Fan et al, 2013;Ishimoto et al, 2016). This different expression profile between gastric cancer and H. pylori infected gastric mucosa suggests that these miRNAs might act differently in the distinct stages of gastric tumorigenesis and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our results showed that miRNAs miR-103, miR-181c, miR-370 and miR-375 are down-regulated in chronic gastritis regardless of H. pylori infection, because both infected and non-infected sample groups had reduced expression of these miRNAs. Other studies have shown down-regulation of miRNAs in inflammatory gastric lesions infected or non-infected by H. pylori (Matsushima et al, 2011;Shiotani et al, 2012); however, in gastric cancer some studies have reported increased expression of miRNAs such as miR-103, miR-181c, miR-370, miR-21 and miR-146a (Wu et al, 2011;An et al, 2013;Fan et al, 2013;Ishimoto et al, 2016). This different expression profile between gastric cancer and H. pylori infected gastric mucosa suggests that these miRNAs might act differently in the distinct stages of gastric tumorigenesis and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that advances have been made over the last decade, the underlying molecular mechanism of gastric cancer metastasis remains obscure [1, 2]. Currently, the signaling pathway in its metastatic cascade has shifted into the spotlight of relevant studies that are organized to find a new treatment for gastric cancer and therefore lower its mortality [3].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), a strain of 22-nt noncoding RNAs, play a decisive role in posttranscriptional gene regulation of gastric cancer, pertaining to cell survival, proliferation, differentiation, migration, invasion and metastasis [2]. For instance, miR-1296 has been proved of its potential linkage with breast cancer chemoresistance and self-renewal capability [4].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of genomic alterations may provide insight into the mechanisms for oncogenic gastric pathways and is important to identify a tumor marker in GC. [26] …”
Section: Introductionmentioning
confidence: 99%
“…[6–8] The Cancer Genome Atlas recently published results of a comprehensive study of GC, which provides an invaluable resource upon which to interpret other related GC findings. A molecular classification scheme in that study defined 4 major genomic subtypes of GC: Epstein–Barr virus (EBV)-infected tumors, microsatellite instability (MSI) tumors, genomically stable tumors, and chromosomal instability (CIN) tumors.…”
Section: Introductionmentioning
confidence: 99%